Factors affecting pregnant women's decisions regarding prenatal pertussis vaccination: A decision-making study in the nationwide Prenatal Pertussis Immunization Program in Taiwan - Wen-Fang Li; Shang-Yu Huang; Hsiu-Huei Peng; Yao-Lung Chang; Shuenn-Dyh Chang; Po-Jen Cheng; Ching-Hua Hsiao; Yi-Ning Su; Tzu-Hung Lin; Chung-Cheng Cheng; Bay-Fong Liu; Ching-Zu Hsieh; et al. (Elsevier, 2020)
Objective: To examine the factors affecting pregnant women's decisions to accept or decline the prenatal pertussis (Tdap) vaccination in Taiwan. Materials and methods: We conducted a cross-sectional survey, recruiting pregnant women who had received prenatal care from eight maternity hospitals between January and December 2018. We examined the participants' demographic characteristics, perceptions of pertussis disease risk and vaccination effectiveness, beliefs regarding vaccine information, physician recommendation, and other potential factors affecting decision-making regarding prenatal vaccination. Results: The complete survey response rate among eligible women was 78%. Among the participants, 74% accepted and 26% declined prenatal Tdap vaccination. Most women accepted Tdap during pregnancy because of perceived severity of pertussis in their infants, perceived effectiveness of the prenatal Tdap in preventing neonatal pertussis, and perceived safety of the prenatal Tdap vaccine for the fetus, as well as a provider's recommendation, which was the factor strongly associated with actual Tdap reception. Most of the participants who accepted Tdap vaccination during pregnancy and who believed that the Tdap vaccine could protect their infants from pertussis reported the receiving sufficient information to make an informed decision and trust in the information. By contrast, a large proportion of the participants who declined Tdap and who did not want to experience possible fetal side effects of Tdap reported not getting sufficient information to make an informed decision and a lack of trust in the information. Conclusion: Developing a comprehensive strategy involving government policy, the health care system, public media, health professionals, and pregnant women to launch a successful campaign may improve the nationwide acceptance of the prenatal pertussis vaccination. Keywords: Pertussis, Vaccine, Prenatal